Colorado history for kids - Wommack, Linda, 1958- (Littleton, Colorado JoyLin Enterprises, 1992)
Colorado history written for children, with illustrations by a fourth grade class at Leroy Elementary in Northglenn, Colorado.
Keywords: Colorado -- History -- Juvenile; Juvenile works